2020
DOI: 10.1111/1756-185x.13975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dehydroepiandrosterone on quality of life in premenopausal women with rheumatoid arthritis: A preliminary randomized clinical trial

Abstract: Aim: Chronic inflammation and subsequent use of glucocorticoids can lead to relative adrenocortical insufficiency in patients with rheumatoid arthritis (RA). Previously, adrenocortical hormone, dehydroepiandrosterone (DHEA) was shown as a potential therapy for autoimmune disorders. However, data regarding effects of DHEA in RA are limited. The aim of this study was to investigate the effects of DHEA on quality of life (QOL) in premenopausal rheumatoid arthritis patients. Method: In this randomized double blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The use of supraphysiological doses had led the RA patients to achieve ACR of 20% in 18% of patients, 35 while the other did not differ from placebo. 34 The only study on fibromyalgia failed to show any benefit. 5 ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of supraphysiological doses had led the RA patients to achieve ACR of 20% in 18% of patients, 35 while the other did not differ from placebo. 34 The only study on fibromyalgia failed to show any benefit. 5 ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some improvement in dryness, fatigue, and quality of life was observed without differences compared to placebo. 29 31 Also, the two studies on RA were not reassuring; 34 , 35 both had a small number of patients (one with 11 and the other with 46 patients), and one used a low dose (50 mg/day) while the other used supraphysiological dose (200mg/day) of DHEA. The use of supraphysiological doses had led the RA patients to achieve ACR of 20% in 18% of patients, 35 while the other did not differ from placebo.…”
Section: Resultsmentioning
confidence: 99%
“…DHEA-S itself has been widely advertised as an over-the-counter supplement that can improve various symptoms related to different conditions, including depression and mood disorders, osteoporosis, adrenal insufficiency, and rheumatoid arthritis [15]. Data in support of these claims remain controversial, with numerous meta-analyses producing inconclusive results [23][24][25][26]. Supplementation with DHEA had a positive effect on the HRQoL in small groups of patients with systemic lupus erythematosus and hypopituitarism [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, two trials of dehydroepiandrosterone (DHEA) have been published. A small open-label trial of DHEA treatment in elderly RA patients (six post-menopausal female and five male) found no benefit on disease activity (98), while a randomized placebo-controlled trial of DHEA in pre-menopausal RA patients (n = 46) found improvements in quality of life but not disease activity scores (99).…”
Section: Androgensmentioning
confidence: 97%